Analysis of genetic diversity and population structure in sweetpotato using SSR markers - Cheng LIU; Ning ZHAO; Zhi-cheng JIANG; Huan ZHANG; Hong ZHAI; Shao-zhen HE; Shao-pei GAO; Qing-chang LIU (Journal of Integrative Agriculture, 2023)
Sweetpotato, Ipomoea batatas (L.) Lam., is an important food crop worldwide. Large scale evaluation of sweetpotato germplasm for genetic diversity is necessary to determine the genetic relationships between them and effectively use them in the genetic improvement. In this study, the genetic diversity of 617 sweetpotato accessions, including 376 landraces and 162 bred varieties from China and 79 introduced varieties from 11 other countries, was assessed using 30 simple sequence repeat (SSR) primer pairs with high polymorphism. Based on the population structure analysis, these sweetpotato accessions were divided into three groups, Group 1, Group 2 and Group 3, which included 228, 136 and 253 accessions, respectively. Consistent results were obtained by phylogenic analysis and principal coordinate analysis (PCoA). Of the three groups, Group 2 showed the highest level of genetic diversity and its accessions were mainly distributed in low-latitude regions. The accessions from South China exhibited the highest level of genetic diversity, which supports the hypothesis that Fujian and Guangdong were the first regions where sweetpotato was introduced to China. Analysis of molecular variance (AMOVA) indicated significant genetic differentiations between the different groups, but low levels of genetic differentiation existed between the different origins and accession types. These results provide valuable information for the better utilization of these accessions in sweetpotato breeding.